The severity of obsessive-compulsive symptoms in Tourette syndrome and its relationship with premonitory urges: a meta-analysis. (1st November 2020) - Yan, Junjuan; Yu, Liping; Wen, Fang; Wang, Fang; Liu, Jingran; Cui, Yonghua; Li, Ying
ABSTRACT: Objectives: Nearly half of the patients with Tourette Syndrome (TS) present with comorbid Obsessive-Compulsive Symptoms (OCS) and premonitory urges (PUs). However, inconsistent results have been found in the correlation between PUs and OCS in patients with TS. Methods: A meta-analysis was applied to identify the severity of OCS and its correlation with PUs in TS patients. Subgroup and meta-regression analyses were used to identify potential heterogeneity. Results: A total of 13 studies, including 576 patients, were enrolled in this study. The pooled correlation coefficient (r) was 0.29 (95% confidence interval: 0.18, 0.38) and heterogeneity (I 2 ) of pooled r was 40% based on a fixed-effect model. The mean level of OCS based on the assessment of Children's Yale-Brown Obsessive-Compulsive Symptom Scale/Yale-Brown Obsessive-Compulsive Symptom Scale was 14.99 (95% CI: 11.41, 18.57) by a random effect model. Results of meta-regression analysis demonstrated that the severity of tic symptoms based on the assessment of the Yale Global Tic Severity Scale was the predictor of severity of OCS ( p = 0.018). Conclusion: There was a mild positive correlation between the PUs and OCS in patients with TS. The severity of OCS in TS patients was mild to moderate and positively predicted by the severity of tic symptoms.